Stockperson attitudes towards Maternity Rings and farrowing crates - Staveley, Lauren M.; Plush, Kate J.; Lines, David S.; Hemsworth, Lauren M.; D’Souza, Darryl N.; van Barneveld, Robert J. (Frontiers in Veterinary Science, 2025)
Societal attitudes suggest low support for confinement housing in livestock farming, such as the farrowing crate. The attitudes of stockpersons working in these systems are yet to be understood but should be prioritised as their human-animal interactions have significant effects on animal welfare. The aim of this investigation was to explore the attitudes of stockpeople employed on pig farms with experience working in both free-farrowing and farrowing crate systems, and to better understand the contributing factors that shape these attitudes. An anonymous survey was conducted across four pig breeder farms with both Maternity Rings (MR) and farrowing crates (FC) installed. A total of 86 stockpeople volunteered to participate. The survey consisted of an opinion-based rating of sow welfare that considered four specific behaviours, and two attitude-based questionnaires. The composite score of sow welfare was higher in a MR when compared to a FC (39.8 ± 0.87 versus 28.0 ± 0.87, p < 0.05), regardless of attitude towards working with sows in different lactation housing systems. Stockpeople that believed FC systems would always be necessary were more likely to avoid interactions with difficult pigs (r(84) = 0.327, p = 0.005), and more likely to rate piglet welfare as more important than sow welfare (r(84) = 0.380, p = 0.001). In contrast, stockpeople that were confident in their abilities and understandings of sow behaviour were more likely to rate the sows welfare higher in a MR (r(84) = 0.339, p = 0.002) and believed that it provided an environment that enabled the sow to better interact with her piglets (r(77) = 0.434, p < 0.001). Stockpersons that were more likely to interact with pigs (r(84) = 0.322, p = 0.011) and were more satisfied with their job (β = 0.341, p = 0.003) were more likely to rate sow welfare higher in a MR. Overall, stockpeople rated sow welfare higher in a MR in comparison to a FC. The main driver of negative attitudes towards a MR appeared to be a lack of understanding of sow behaviour. If we can develop ways to modify stockperson behaviour to improve sow and piglet welfare outcomes, we have a better chance of introducing alternative farrowing systems.